An Examination of Policies Addressing Human Trafficking in Tanzania - Magesa, Rehema John (Journal of Social and Community Development, 2024)
Human trafficking remains a pervasive global issue, often hidden under various forms of exploitation, and continues to impact millions worldwide. Frequently termed modern-day slavery, it is a grave violation of human rights with long-lasting, devastating consequences for its victims. Effective policies are crucial in the fight against this inhuman practice, focusing on preventing exploitation, protecting at-risk populations, and delivering justice to victims. In Tanzania, numerous policies and laws have been implemented to combat human trafficking. Despite this robust policy framework, the country remains under Tier II of the U.S. Department of State's Trafficking in Persons (TIP) report, signaling that trafficking persists as a serious concern. This study sought to critically examine the effectiveness of the current policies addressing human trafficking in Tanzania from a qualitative perspective. The findings highlighted that Tanzania has developed a strong and comprehensive policy approach aimed at protecting victims, preventing trafficking, and prosecuting perpetrators. However, while the legal and institutional frameworks are in place, challenges remain in their execution. The efforts to combat human trafficking are hindered by inadequate resources, weak coordination among stakeholders, and gaps in the enforcement of laws. These deficiencies limit the overall impact of Tanzania's anti-trafficking initiatives, allowing the issue to persist despite the country’s commitment. The study underscores the need for improved resource allocation, better coordination mechanisms, and stricter enforcement procedures to fully realize the goals of Tanzania's anti-trafficking policies and effectively reduce the prevalence of this heinous crime.